Stroke in Hemodialysis Patients Randomized to Different Intravenous Iron Strategies: A Prespecified Analysis from the PIVOTAL Trial. Issue 11 (25th November 2021) - Mark, Patrick B.; Jhund, Pardeep S.; Walters, Matthew R.; Petrie, Mark C.; Power, Albert; White, Claire; Robertson, Michele; Connolly, Eugene; Anker, Stefan D.; Bhandari, Sunil; Farrington, Kenneth; Kalra, Philip A.; et al.
Visual Abstract: Abstract : Key Points: In analysis of the PIVOTAL trial, proactive intravenous iron dosing was not associated with increased stroke risk in patients on hemodialysis. Risk factors for stroke included diabetes, prior stroke, higher BP, lower serum albumin, inflammation, and women. Mortality of stroke was high; 58% of patients with a stroke event died during follow-up compared with 23% without a stroke. Background: People with kidney failure treated with hemodialysis (HD) are at increased risk of stroke compared with similarly aged people with normal kidney function. One concern is that treatment of renal anemia might increase stroke risk. We studied risk factors for stroke in a prespecified secondary analysis of a randomized, controlled trial of intravenous iron treatment strategies in HD. Methods: We analyzed data from the Proactive IV Iron Therapy in Haemodialysis Patients (PIVOTAL) trial, focusing on variables associated with risk of stroke. The trial randomized 2141 adults who had started HD <12 months earlier and who were receiving an erythropoiesis-stimulating agent (ESA) to high-dose IV iron administered proactively or low-dose IV iron administered reactively in a 1:1 ratio. Possible stroke events were independently adjudicated. We performed analyses to identify variables associated with stroke during follow-up and assessed survival following stroke. Results: During a median 2.1 years of follow-up, 69 (3.2%) patients experienced a first postrandomization stroke. Fifty-seven (82.6%) were ischemic strokes, and 12 (17.4%) were hemorrhagic strokes. There were 34 postrandomization strokes in the proactive arm and 35 postrandomization strokes in the reactive arm (hazard ratio, 0.90; 95% confidence interval, 0.56 to 1.44; P =0.66). In multivariable models, women, diabetes, history of prior stroke at baseline, higher baseline systolic BP, lower serum albumin, and higher C-reactive protein were independently associated with stroke events during follow-up. Hemoglobin, total iron, and ESA dose were not associated with risk of stroke. Fifty-eight percent of patients with a stroke event died during follow-up compared with 23% without a stroke. Conclusions: In patients on HD, stroke risk is broadly associated with risk factors previously described to increase cardiovascular risk in this population. Proactive intravenous iron does not increase stroke risk. Clinical Trial registry name and registration number: Proactive IV Iron Therapy in Haemodialysis Patients (PIVOTAL), 2013-002267-25